Positive sequence reactive current differential protection of transmission lines connected to energy storage power station - Zhu, Haoyu; Wang, Xiaoran; Fan, Chunju; Hu, Yan; Tai, Nengling (Frontiers in Energy Research, 2025)
When the energy storage power station encounters a fault on the transmission line during charging, active component of its short-circuit current still maintains an inverse relationship with the positive-sequence voltage at its grid connection point, influenced by the converter control strategy. This leads to a large phase difference between the short-circuit currents on both sides of the transmission line, posing a risk of no-trip failure in conventional current differential protection. To address the above issues, this paper proposes a differential protection scheme for transmission line connected to energy storage power stations based on positive-sequence reactive current, which can effectively avoid the influence of energy storage charging and discharging state on the differential current protection. The feasibility of the positive-sequence reactive current differential protection for transmission line connected to energy storage power station is analyzed through theoretical derivation. To address the issue of protection sensitivity being affected by line capacitive current when the fault voltage drop is relatively low, capacitive current compensation is added to the positive-sequence reactive current differential protection criterion. Finally, performance testing was conducted through PSCAD simulation. Results show that the proposed method can eliminate the impact of energy storage charge and discharge differences on the current differential protection performance and has good performance under different fault conditions.